Preparation of quinoa bran dietary fiber-based zinc complex and investigation of its antioxidant capacity in vitro - Wei, Chunhong; Wang, Xinhui; Jiang, Xiujie; Cao, LongKui (Frontiers in Nutrition, 2023)
In this study, a four-factor, three-level response surface optimization of quinoa bran soluble dietary fiber (SDF) complexation of zinc was studied. The effect used four factors on the chelation rate was investigated: (A) mass ratio of SDF to ZnSO4.7H2O, (B) chelation temperature, (C) chelation time, and (D) pH. Based on the results of the single-factor test, the four-factor three-level response surface method was used to optimize the reaction conditions. The optimal reaction conditions were observed as mentioned here: the mass ratio of quinoa bran SDF to ZnSO4.7H2O was 1, the reaction temperature was 65℃, the reaction time was 113 min, and the pH of the reaction system was 8.0. The average chelation rate was 25.179% under optimal conditions. The hydration method rendered a fluffy quinoa bran SDF structure. The intramolecular functional groups were less stable which made the formation of the lone pairs of electrons feasible to complex with the added divalent zinc ions to form a quinoa bran soluble dietary fiber-zinc complex (SDF-Zn). The SDF-Zn chelate had higher 2,2-diphenylpicrylhydrazyl (DPPH), ABTS+, hydroxyl radical scavenging ability, and total antioxidant capacity. Therefore, metal ion chelation in dietary fiber is of biological importance.